A Study on Flipped Learning Concerning Learning Motivation and Learning Attitude in Language Learning - Chou, Chi-Pu; Chen, Kuo-Wei; Hung, Chia-Jen (Frontiers in Psychology, 2021)
From the popularity of flipped teaching in the US primary and high schools, it is sighted that students have more learning control to adjust to the learning progress and are assisted in problem solving and learning guidance during class period. It is believed that flipped teaching could prompt underachievement learners’ active learning and thereby enhance learning effectiveness. A total of 386 high school students in Chung Li, Taiwan, were part of an experimental study and the research results are summarized below: 1. Students who participate in the flipped teaching models demonstrate better comprehension levels with the teaching content due to this change in learning style and attitude, which in turn, enhances learning effectiveness. 2. To eliminate poor language performance of underachieving students, it is necessary to lay solid foundations to gradually enhance language learning effectiveness regarding this particular group of students. Films suitable for students’ individual ability could be combined with new language learned in the unit to genuinely assist underachieving learners’ language learning effectiveness. 3. For students who care about their performance, a ‘system of play’ style grouping should be determined in order to enable the tracking of group performance and term performance. According to the results, further developments regarding active learning ability, boosts in learning interests, enhanced learning effectiveness, and the prompting of creativity resulting in a shift from passive learner to active learner have been sighted.